Validity and reliability of the oral case presentation skills audit - P Boonluksiri; L Haura; B Warachit (Journal of Health Science and Medical Research (JHSMR), 2005)
Objective: To investigate the validity and reliability of audit of medical students' problem-solving skills by oral presentation and the students' satisfaction with this learning experience. Meterial and Methods: Thirty eight 5th year medical students rotating to study "Health and Disease From Conception to Adolescence" were assigned to present and discuss their patients' problems in the classroom for audit. They received immediate feedback after their presentation. The analytic rubric scorings were (1) history and physical exam data, (2) problem listing, (3) differential diagnosis, (4) analysis with reflective reasoning, (5) plan for management, and (6) appropriate language and time. The students' assessment of their satisfaction was obtained after their presentation. Results: The oral case presentation with common problems selected by students from their patients was rated with a moderate to high degree of content validity. For construct validity consideration, the scores were rated by 2 raters and were analyzed for correlation and reliability. The result showed that analysis with reflective reasoning, plan for management, appropriate language & time, and total scores had reliability coefficients of 0.56, 0.73, 0.57, and 0.70 respectively. The students were satisfied with this learning experience. Conclusion: The audit of problem-solving skills by oral case presentation is a useful learning experience for medical students, with a moderate degree of validity and reliability. The students' satisfaction with this learning experience is high overall.